ANALISIS SISTEM PADA NFT (NON-FUNGIBLE TOKEN) DAN PERKEMBANGANNYA DALAM DUNIA BISNIS - Julianto, Julianto (LPPM Universitas Bina Bangsa, 2023)
The purpose of this research is to describe and explain the latest developments in NFT which are digital assets that can be owned digitally using blockchain technology where the blockchain system maintains ownership and certificates of NFT Tokens including spying on every transaction and ownership of NFTs. NFT allows a digital work/asset to be owned by all users as long as the asset does not change hands to other users, because NFT can be transferred by the original voters. NFTs can be in the form of works of art, such as game assets, photos, videos, music, and so on. NFT can be traded or auctioned in many existing NFT marketplaces, such as opensea, rarible, axie infinity. The selling price of the NFT depends on subjective factors such as the quality, creativity and reputation of the artist. The more unique, interesting, an NFT work and well-known creator, the higher the value of the NFT token price will be. The way NFT works is that its digital data storage system will allow users to transfer data confidentially to each other, through encryption schemes in cryptography, so that data cannot be confidential and owned by other users, because they do not own the data